SISTEM INFORMASI PENGELOLAAN STOK BARANG BERBASIS WEB PADA TOKO LISTRIK XYZ - Dany Sentiana (2022)
For business owners, inventory is a crucial thing to pay attention to, therefore it is necessary to manage stock as well as possible in order to avoid various adverse problems. Stock data management by XYZ electrical shop is not optimal, this causes various problems in the store. To solve this problem the author wants to build a web- based information system for stock management, the system development method used in the design is waterfall with the hope that the resulting information system will work properly, and the information system applies the ABC calculation method and the Min -Max method to control the inventory of an item, the information system is web-based which was built using the PHP programming language and utilizes MySQL as a database and Apache as a server. The design of the stock management information system aims to assist the store in carrying out all activities related to stock management.